Can cyclic voltammetry at microdisc electrodes be approximately described by one-dimensional diffusion? - Alden, J; Hutchinson, F; Compton, R (1997)
Fast scan cyclic voltammetry using microdisc electrodes is now widely employed for the study of the kinetics and mechanism of electrode processes. For convenience, it is common for experimentalists to interpret the results assuming that the disc can be treated as either a planar or a hemispherical electrode. Both approximations are available in the now widely adopted one-dimensional simulation package DigiSim which can simulate the cyclic voltammetric response of arbitrarily complex reaction mechanisms. This paper critically addresses the validity of this simplification. To this end, the application of the strongly implicit procedure (SIP) is developed to simulate transient processes at microdisc electrodes. The approach is validated by the simulation of chronoamperometric transients resulting from potential steps at microdisc electrodes; excellent agreement is obtained with analytical and other simulation methods. The simulation method is then used to model the cyclic voltammetric response of electrochemically reversible processes at microdisc electrodes. Corresponding simulations are reported for microhemisphere electrodes using the backwards implicit in time (BIT) method, allowing comparison between the two electrode geometries so that limitations of treating voltammetry at microdisc electrodes by approximation to a one-dimensional (hemispherical) diffusion problem can be quantified. Strong reservations are expressed about the approximation under transient conditions.